Macroporous Directed and Interconnected Carbon Architectures Endow Amorphous Silicon Nanodots as Low-Strain and Fast-Charging Anode for Lithium-Ion Batteries - Li, Zhenwei; Han, Meisheng; Yu, Peilun; Lin, Junsheng; Yu, Jie (Nano-Micro Letters, 2024)
Fabricating low-strain and fast-charging silicon-carbon composite anodes is highly desired but remains a huge challenge for lithium-ion batteries. Herein, we report a unique silicon-carbon composite fabricated by uniformly dispersing amorphous Si nanodots (SiNDs) in carbon nanospheres (SiNDs/C) that are welded on the wall of the macroporous carbon framework (MPCF) by vertical graphene (VG), labeled as MPCF@VG@SiNDs/C. The high dispersity and amorphous features of ultrasmall SiNDs (~ 0.7 nm), the flexible and directed electron/Li+ transport channels of VG, and the MPCF impart the MPCF@VG@SiNDs/C more lithium storage sites, rapid Li+ transport path, and unique low-strain property during Li+ storage. Consequently, the MPCF@VG@SiNDs/C exhibits high cycle stability (1301.4 mAh g−1 at 1 A g−1 after 1000 cycles without apparent decay) and high rate capacity (910.3 mAh g−1, 20 A g−1) in half cells based on industrial electrode standards. The assembled pouch full cell delivers a high energy density (1694.0 Wh L−1; 602.8 Wh kg−1) and an excellent fast-charging capability (498.5 Wh kg−1, charging for 16.8 min at 3 C). This study opens new possibilities for preparing advanced silicon-carbon composite anodes for practical applications. Highlights: 1 MPCF@VG@SiNDs/C, constructed by uniformly dispersing amorphous Si nanodots in carbon nanospheres that are welded on the wall of the macroporous carbon frameworks by vertical graphene, is synthesized and has achieved a few kilogram production per batch. 2 Finite element imitation reveals that amorphous Si nanodots with high dispersity in carbon nanosphere can achieve ultra-low stress and strain values during lithiation. 3 Unique low-strain property and fast-charging capability are achieved under industrial electrode conditions.